When day breaks ebook - Banks, Maya (KGI, 2014)
THE ALL-NEW KGI NOVEL BY NEW YORK TIMES BESTSELING AUTHOR AUTHOR MAYA BANKS The Kelly Group International (KGI): A super-elite, top secret, family-run business. Qualifications: High intelligence, rock-hard body, military background. Mission: Hostage/kidnap victim recovery. Intelligence gathering. Handling jobs the U.S. government can’t… Eden is said to be one of the most beautiful women in the world. Her face has graced countless magazines and her body has sold millions of dollars of clothing. But her fame and beauty has earned her more than she ever imagined. Evil is stalking her, determined to extinguish the ethereal beauty forever. Swanson or “Swanny” as his teammates call him is always up for the next mission. He came back from Afghanistan wounded and scarred. Hardly the kind of man who even belongs in the same room with Eden. And yet there’s something about the quiet beauty that stirs his blood and makes him dream of the impossible. Because Beauty loving the Beast only happens in fairy tales and KGI doesn’t deal in fairy tales. Ever.